Design of Wideband Slot Antenna Array with Stereoscopic Differentially Fed Structures - Guang Sun; Ge Gao; Tingting Liu; Yi Liu; Hu Yang (International Journal of Antennas and Propagation)
In this paper, a wideband slot antenna element and its array with stereoscopic differentially fed structures are proposed for the radar system. Firstly, a series of slots and a stereoscopic differentially fed structure are designed for the antenna element, which makes it possess a wide bandwidth, stable radiation characteristics, and rather high gain. Moreover, the stereoscopic feeding structure can firmly support the antenna’s radiation structure and reduce the influence of feeding connectors on radiating performance. Secondly, a 4 × 4 array is designed using the proposed antenna element. And a hierarchical feeding network is designed for the array on the basis of the stereoscopic differentially fed structure. For validation, the antenna element and 4 × 4 array are both fabricated and measured: (1) the measured −10 dB impedance bandwidth of the antenna element is 62% (6.8–12.9 GHz) and the gain within the entire band is 5–9.7 dBi and (2) the measured −10 dB impedance bandwidth of the array is approximately 50% (7 to 12 GHz) with its gain being 14–19.75 dBi within the entire band. Notably, measured results agree well with simulations and show great advantages over other similar antennas on bandwidth and gain.